Produção e caracterização de nanocompósitos poliméricos à base de resina acrílica odontológica reforçada com nanocristais de celulose modificados, e não modificados, superficialmente com anidrido maleico. - Silvério, Hudson Alves (2017)
Resins constituted, basically, by methacrylate polymers are widely used in the manufacture of dental prostheses. Cellulose nanocrystals (CN), due to their intrinsic properties such as stiffness and high surface area, have been used as reinforcing agent in several polymer matrices. However, CNs are hydrophilic, which makes it difficult to apply them to non-hydrophilic or low hydrophilic matrices. Thus, chemical modifications are necessary through the substitution of hydroxyl groups on the surface of the CN by other groups that can help in the dispersion and compatibilization of CN with these matrices. In this work CN were extracted from Kraft pulp (Eucalyptus urograndis) by acid hydrolysis in three different reaction times to choose the best reinforcement element for a commercial dental acrylic resin (PEMA RESIN). The results showed that CN extracted with the time of 55 minutes (NC55) presented higher aspect ratio and crystallinity index and, therefore, were selected as best reinforcing agent. In an attempt to improve the dispersion of these nanoparticles in the polymer matrix under study, chemical modifications were performed on the surface of NC55, using 20 and 100 mg of maleic anhydride (MA) for each gram of cellulosic material, resulting in the nanoparticles NCmod1 and NCmod2 respectively. The proof of the modifications performed were evaluated in the FTIR spectra through a new band centered around 1730 cm-1 attributed to the stretches of the vibrations of the C = O carbonyl groups of acids and / or esters. The effects caused by the modifications were analyzed by the morphology, crystallinity, thermal stability and degree of polymerization of the produced nanoparticles. Nanocomposites were produced by in situ incorporation of NC in the reaction medium during the polymerization of PEMA RESIN ( in situ method ) and by incorporation of NC in the polymer matrix after polymerization (ex situ method), in which the nanocomposites in general presented superior mechanical performance over PEMA RESIN. The nanocomposites, produced by in situ polymerization with 1.0 % w/w of the chemically modified nanoparticles, reinforced the matrix more effectively in both flexural analysis (Fs), 50% higher than the matrix, as in the dynamic mechanical thermo analysis (DMTA), 42% greater than the matrix. The nanocomposites produced in the same percentage of NC55 and NCmod1, by ex situ method had better performance in DMTA analysis, 47 and 53% higher than the polymer matrix, than the corresponding nanocomposites produced by in situ polymerization. The incorporation of chemically modified or unmodified CN through the in situ polymerization methodology in PEMA RESIN provided visible mechanical reinforcements, especially when modified reinforcement was used that has the ability to chemically bond to the matrix through the unsaturation of the modifying group added on its surface. The method of ex situ incorporation proved to be superior in the DMTA analysis due to the good dispersion and adhesion of the nanocrystals in the matrix and also to the fact that in this method of production of nanocomposites the CN are not in the reaction medium of the matrix polymerization and so they do not interfere and do not limit this process, thus not altering the molar mass of the matrix. The present study showed that the incorporation of CN may represent an alternative to maximize the mechanical properties of acrylic resins.